2008
DOI: 10.1016/j.cellsig.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Kit- and FcɛRI-induced differential phosphorylation of the transmembrane adaptor molecule NTAL/LAB/LAT2 allows flexibility in its scaffolding function in mast cells

Abstract: The transmembrane adaptor protein (TRAP), NTAL, is phosphorylated in mast cells following FcvarepsilonRI aggregation whereby it cooperates with LAT to induce degranulation. The Kit ligand, stem cell factor (SCF), enhances antigen-induced degranulation and this also appears to be NTAL-dependent. However, Kit and FcvarepsilonRI appear to utilize different mechanisms to induce NTAL phosphorylation. Thus, we examined whether the responsible kinases selectively phosphorylated distinct tyrosines in NTAL and explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 42 publications
2
66
1
Order By: Relevance
“…PAG-WT cells released increasing amounts of ␤-glucuronidase when activated with 25 to 200 ng/ml SCF. The extent of SCF-induced degranulation was higher than that described in previous studies (50,51) and was apparently related to the growth of bone marrow cells in the presence of both IL-3 and SCF. When BMMCs were derived from cultures containing IL-3 alone, their SCF-induced degranulation was low (45).…”
Section: Resultscontrasting
confidence: 43%
“…PAG-WT cells released increasing amounts of ␤-glucuronidase when activated with 25 to 200 ng/ml SCF. The extent of SCF-induced degranulation was higher than that described in previous studies (50,51) and was apparently related to the growth of bone marrow cells in the presence of both IL-3 and SCF. When BMMCs were derived from cultures containing IL-3 alone, their SCF-induced degranulation was low (45).…”
Section: Resultscontrasting
confidence: 43%
“…Thus, c-Kit can phosphorylate NTAL directly, whereas FceRI only indirectly through Lyn or Syk kinase. Importantly, Syk and c-Kit phosphorylate different tyrosines in NTAL, which then serve as direct or indirect binding sites for different kinases, phosphatases and other enzymes [10]. Different ways of cell activation could lead to formation of different NTAL signalosomes and therefore different performance of the cells in such complex processes as migration, spreading and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…After c-kit receptor engagement, NTAL becomes phosphorylated. In human and murine mast cells, FceRI-and SCF-mediated NTAL phosphorylations are regulated differentially by Src family kinases and c-kit, respectively [10].…”
Section: Introductionmentioning
confidence: 99%
“…SH2 domain containing leukocyte protein of 76 kDa is needed for FcgR-mediated ROS production in neutrophils (13), but not in macrophages (14,15), which may be because of differential FcgR expression. Linker for activation of T cells (LAT) and LAT2 can be phosphorylated by Syk and Src kinase Lyn (16,17) and have been shown to be critically involved in myeloid ITAM signaling (18)(19)(20). It has been suggested that FcgRI, but not FcgRIIa, cross-linking leads to phosphorylation of LAT2 in the human monocytic cell line THP-1.…”
Section: Fcgri Downstream Signalingmentioning
confidence: 99%